Immobilisation of torus fractures of the wrist in children (FORCE): a randomised controlled equivalence trial in the UK - Perry, DC; Achten, J; Knight, R; Appelbe, D; Dutton, SJ; Dritsaki, M; Mason, JM; Roland, DT; Messahel, S; Widnall, J; Costa, ML (Elsevier, 2022)
Background The most common fractures in children are torus (buckle) fractures of the wrist. Controversy exists over treatment, which ranges from splint immobilisation and discharge to cast immobilisation, follow-up, and repeat imaging. This study compared pain and function in affected children offered a soft bandage and immediate discharge with those receiving rigid immobilisation and follow-up as per treating centre protocol.